Competition or reciprocity? A study on the symbiosis of effective knowledge management between MNCs and non-MNCs. Issue 4 (8th March 2021) - Hu, Yelin; Zhang, Qiwang; Yang, Zhen; Huang, Sujian
Abstract : Purpose: The purpose of this paper is to explore the relationship between effective knowledge management and corporate performance, to explore the dynamic symbiosis phenomenon of effective knowledge management based on organizational ecology with multinational companies (MNCs) and non-multinational companies (non-MNCs) and to explore the symbiosis strategy of knowledge management between multinational and non-multinational companies (non-MNCs) in China. Design/methodology/approach: To measure effective knowledge management, this paper first uses structural equation model to measure knowledge management, based on the evolution dynamics equation in organizational ecology to measure the effectiveness of knowledge management, and studies the symbiosis of effective knowledge management between MNCs and non-MNCs based on ecological perspective. Findings: Effective knowledge management can promote the financial performance of enterprises, but different degrees of effectiveness have different effects. In addition, the coupling and collaboration between knowledge management and corporate performance can reflect the value of effective knowledge management. The results show that effective knowledge management plays a positive moderating effect between knowledge management and corporate performance. Finally, the effective knowledge management system of MNCs (non-MNCs) has negative effect on non-MNCs (MNCs), showing the exclusive relationship between MNCs and non-MNCs in China. Research limitations/implications: The effectiveness of knowledge management is only based on the measurement of financial performance coupling. For other types of performance, it needs to be tested. The samples may not cover symbiosis relationship of effective knowledge management in other countries. Practical implications: This paper provides practical and theoretical reference for confirming the symbiotic interaction and identifying the opportunities and challenges of knowledge management among different types of corporation groups. Originality/value: The paper is one of the pioneering studies to explore the pattern of symbiotic evolution of effective knowledge management between MNCs and non-MNCs. From completely new perspectives, this study advances the research of knowledge management to a new and promising area.